Concurrent chemoradiotherapy with low dose weekly gemcitabine in stage III non-small cell lung cancer - YUMUK, PERRAN FULDEN (BMC, 2005)
Background: Combined chemoradiotherapy (CRT) is the treatment of choice for stage III NSCLC. Gemcitabine (G) is a novel deoxycitidine analogue that has been proven to be a potent radiosensitizer. Twenty-two consecutive patients were treated with concurrent CRT to demonstrate the tolerability and efficacy of low dose G given weekly as radiosensitizer in stage III NSCLC. Methods: Patients with KPS >= 70, adequate bone marrow reserve, with no prior radiotherapy (RT) and surgery were included. Eighteen patients had received prior induction chemotherapy (CT). G (75 mg/m(2)/week) was infused over 1 hour for 6 weeks. Thoracic RT was given two hours later over 6 weeks at 1.8 Gy/day fractions (total dose of 61.2 Gy). Pulmonary toxicity was evaluated with computed tomography scans in 6 weeks. Results: Median age was 60 years (range, 48-75), median follow-up was 15 months (range, 2-40). Sixty-eight percent of patients were male and median KPS score was 90. Conformal 3D-RT planning was used in 64% of patients. G was given for a median of 5 weeks ( range 1-9). Twelve patients (54.6%) received all planned CT. G was stopped because of intolerance in 6 and death in 2 patients. Seven patients (31.8%) had radiation pneumonitis. Twenty patients were evaluated for overall response, 1 patient (4.5%) had clinical CR, 81.8% had PR while 9.5% had SD. Median overall survival (OS) was 14 +/- 5 months (95% CI 3-25). One- and 2-year OS rates were 55% and 38%. Sixteen patients died of disease-related events (6 with progression of primary tumor, 8 due to metastatic disease), 2 patients died of other causes. One- and 2-year progression- free survival and local control rates were 56%, 27% and 79%, 51%, respectively. Conclusion: G might be used as radiosensitizer for patients with stage III NSCLC who could not receive full doses CT with concurrent RT.
Keywords: TWICE-WEEKLY GEMCITABINE; LEUKEMIA GROUP-B; PHASE-I TRIAL; RADIOTHERAPY; CHEMOTHERAPY; RADIATION; PACLITAXEL; CISPLATIN; RADIOSENSITIZATION; SURVIVAL